OPTIMIZING DIGITAL TEACHING RESOURCES TO IMPROVE THE QUALITY OF ISLAMIC RELIGIOUS EDUCATION IN HIGH SCHOOL - Fauzan Huda Perdana; Udin Supriadi; Pandu Hyangsewu (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study explores how optimizing digital teaching resources can improve the quality of Islamic Religious Education (IRE) in high schools. Using a descriptive qualitative method, including interviews, observations, and document analysis, the research examines teachers' strategies in planning, integrating, and evaluating digital tools, as well as their role in boosting students' interest, motivation, creativity, and understanding. Findings indicate that digital resources such as e-books, instructional videos, Learning Management Systems (ELMU), school websites, interactive quizzes (Quizizz, Kahoot), and online communication forums positively influence IRE learning effectiveness. These resources support more interactive, contextual, and collaborative learning experiences, which enhance student engagement and Islamic character development. Nonetheless, challenges such as limited infrastructure, teachers' digital literacy, and uneven internet access persist. To address these issues, ongoing training, institutional support, and improved internet facilities are essential so all students can access learning equally. The study's outcomes aim to guide the development of a relevant, innovative, and sustainable digital-based IRE learning model amid the ongoing digital education transformation.